THE EFFECT OF EMPLOYEE MOTIVATION AND JOB SATISFACTION ON HUMAN RESOURCE MANAGEMENT - BAHIROH, ELOH; ARTHAWATI, SRI NDARU (Management Science Research Journal, 2023)
Job satisfaction is a general attitude towards one's work, which shows the difference between the number of awards received by workers and the amount that workers believe they should receive. The purpose of this research to analyze the importance of employee motivation and job satisfaction on human resource management. The research methods using statistics descriptive analyze and regression analysis to determine the correlation between independent and dependent variable. The sample were be taken from 100 sample of employee selected by saturated sampling techniques. The data has been collected by questionnaire. The results shows that motivation (X1) and job satisfaction (X2) influence on human resource management (Y)